Analysis of molecular links between epigenetic regulations and energy metabolism - Miezaniec, Agata (2020)
Oxidation of fatty acids is an important energy source for skeletal muscle and heart, particularly during aerobic exercise and long-term fasting, and requires L-carnitine. L-carnitine has important roles in metabolism including cellular acetyl- and acyl-transport; its disorders lead to cardiomyopathy and skeletal muscle weakness. Carnitine is biosynthesized from trimethyllysine, whose only cellular sources are histones and other proteins containing trimethylated lysines. Surprisingly to date, this link between epigenetics and energy metabolism has received little attention. This work investigated the fundamental question of whether protein methylation modulates fatty acid metabolism via carnitine biosynthesis. Specific objectives included the role of individual methyltransferase substrates for carnitine metabolism, the role of protein degradation in this pathway and its manipulation by small molecules. An optimised high-pressure liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) method allowed for detection and quantification of carnitine and fatty acid metabolites from whole lysates of yeast and human cells exposed to genetic or pharmaceutical modulators. The key result was that genetic deletion of individual protein methyltransferases affected cellular carnitine levels. That effect was also observed by treatment with hypomethylating agents, with clinically used iron chelators and anti-obesity drugs. Together with time-scale studies, these results suggested that it may be possible to modulate carnitine levels via changes in protein methylation status.